Management Strategies of a Productive Waqf-Based Forest in Bogor, Indonesia - Jannah, Miftahul; Sarkawi, Azila Ahmad; Othman, Jamilah; Ali, Khalifah Muhamad (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Waqf-based forest is developed on waqf land and is now being developed in Indonesia. It combines Islamic principles with environmental conservation, as being waqf assets, a forest is prohibited from being sold, given, or inherited. An effective management strategy is crucial to ensure waqf-based forest productivity and sustainability. Some research has already been conducted, but the specific dimension remains unexplored. This study aims to identify essential aspects and effective management strategies to escalate waqf-based forest benefits. Using a comprehensive approach, this study combines a literature study, in-depth interviews, and a study case in Bogor Waqf Forest, Bogor Regency, Indonesia. The findings were analyzed using the Analytic Hierarchy Process (AHP), followed by Focus Group Discussion (FGD) and further in-depth interviews as the validation process. There are six important considerations to optimize waqf-based forest management: legal, ecological, Islamic, economical, social, and aesthetic. The land’s legal status as waqf assets is recognized as the most crucial aspect to avoid possible conflict and sustainability in the future. Then, the following considerations are improved ecological and Islamic activities aspects, economic strategies, and social and aesthetic consecutively. This research is expected to provide a deeper investigation of the future management strategies for waqf-based forests. Keywords: agroforestry, analytic hierarchy process, management, sustainability, waqf-based forest